When Do Natural Resources Harm Fiscal Health? Evidence from the United States. Issue 6 (6th November 2018) - Carr, Douglas A.; Fails, Matthew D.
Abstract : Do natural resources have harmful economic consequences? This question is central to the interdisciplinary "resource curse" literature, but important questions remain unanswered. At the same time, the discovery of new resource deposits around the world and technological developments that enable greater resource extraction make understanding the dynamics of the resource curse even more pressing. This article addresses these issues by focusing on the relationship between resource abundance and fiscal outcomes, which we argue more accurately reflects the causal mechanisms emphasized in existing research than aggregate economic outcomes like increases in gross domestic product per capita. We describe a variety of hypotheses linking resource abundance to fiscal health, including how political and institutional factors can either mitigate or exacerbate the effect of resource wealth, and test these arguments using state‐level data from the United States encompassing the years 1992‐2014. This focus on subnational variation helps minimize some of the limitations of the cross‐country comparisons that have dominated the prior literature. Our regression results suggest that, contrary to the most pessimistic theories, resource wealth is often associated with stronger fiscal performance at the state level. However, a number of factors, including levels of political polarization, legislative term limits, and lower wage growth, negate these benefits. Related Articles: Khodr, Hiba .2014 . "A Preliminary Comparative Study of Policy Making in Two GCC Countries – Qatar and Kuwait: Processes, Politics, and Participants ."Politics & Policy 42 (2 ):271 ‐310 .https://doi.org/10.1111/polp.12068 Day, Jonathan, andKeith Boeckelman .2012 . "The Impact of Legislative Term Limits on State Debt: Increased Spending, Flat Revenue ."Politics & Policy 40 (2 ):320 ‐338 .https://doi.org/10.1111/j.1747-1346.2012.00347.x Prier, Eric, andKevin Wagner .2009 . "Running Unopposed: Assessing the Impact of Term Limits on Competition in Florida and Maine ."Politics & Policy 37 (1 ):101 ‐125 .https://doi.org/10.1111/j.1747-1346.2008.00163.x